‘Stranger in the Dark’ : a comparative analysis of the reporting of rape cases against minors in Malay and English newspapers in Brunei and Malaysia - Sharifah Nurul Huda Alkaff; McLellan, James (Penerbit Universiti Kebangsaan Malaysia, 2018)
Journalists of Malay and English newspapers from Brunei and Malaysia are found to adopt different stances in terms of their inclusion of detail and their level of involvement or detachment in crime and accident reports. This study combines an analysis of online news reports of rape cases with interview data from journalists and editors of Malay and English newspapers in Brunei and Malaysia. Our original hypothesis is that Malay news reports would demonstrate a more restrained approach to crime and accident news compared to English news stories. Four parallel pairs of rape stories from four newspapers were analysed using Fairclough’s (1995) framework and van Leeuwen’s (2008) representation of social actors and social action approach. Critical case purposive sampling method was used to collect the news stories. The findings reveal clear differences in how rape cases are reported by the Malay newspapers vis-à-vis their English counterparts, with reports in the Malaysian Malay paper, for example, being longer and containing more details of the crimes while the opposite is found in the Bruneian Malay paper. Our findings suggest that differences in the reporting of rape cases are not just due to linguistic differences but are culturally, ideologically and politically situated.